Estudio sobre las redes de soporte social de niños trabajadores en Lima Metropolitana - Franco, Rocío (1989)
This paper deals with a descriptive study on social support networks in 30 working children and 30 non working children. Their average age was 9 years, all of them lived with their parents in urban marginal zones of Lima, and assisted regularly to school. The results show that social networks of working children have a tendency to be wide and that their exchange relationship is based on functional and concrete aspects. It was also found that the adult members of the network maintained non satisfactory relationships with the children. As a consequence adults do not have a significant presence in the network. Parents maintain their presence due to stability and facility of their access. These characteristics belong exclusively to working children.